(untitled) (Research, Society and Development, 2020)
For this comparative study, a financial institution was used as a multiple bank and a credit cooperative, in which three essential products were analyzed for these different financial institutions of multiple portfolios within the investment area when working with a fixed income product and also with two products in the area of loans. The research was exploratory, descriptive and explanatory, starting from a case study, which was developed through the application of a semi-structured form for the analyzed financial institutions. Thus, the main objective of the present work was to carry out a mapping highlighting the advantages and disadvantages of a multiple bank and a credit cooperative, considering for analysis the Certificate of Deposit; the New Vehicle Financing and the Working Capital or Revolving Credit, with the intention of presenting relevant information to a company that intends to establish business relations with one of these institutions.